2022
DOI: 10.19044/esipreprint.10.2022.p776
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Learning and Professional Development: Views and Practices of Georgian and Turkish Teachers of English

Abstract: By the time they graduate from their initial teacher education programs, most teachers are equipped with the basic information and skills they will need to begin their classroom practice – including content knowledge, theories about the teaching and learning process, and various instructional strategies and techniques. However, the process of becoming a teacher does not end there. The most successful teachers are also lifelong learners who continuously work to improve their subject-related knowledge, understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This distinction between workplace learning and learning in institutes of education reflects the broad distinction between training and education, where education provides the theoretical knowledge, and training shows how to apply the knowledge in practice (Barnes, 2014;Blair & Serafini, 2016;Masadeh, 2012;Rickman, 2004), although the distinction between training and education is not universally agreed, see for example Hager and Laurent (1990), and each term can be parsed in greater detail, for example in Garavan (1997). The importance of workplace learning is demonstrated in a survey of Finnish university graduates conducted by Tynjälä et al (2006), which revealed that 64 percent of the 990 respondents considered they had learned the most important skills for their jobs at work, rather than at university, while just 14 percent thought they had learned the skills at university.…”
Section: Introductionmentioning
confidence: 99%
“…This distinction between workplace learning and learning in institutes of education reflects the broad distinction between training and education, where education provides the theoretical knowledge, and training shows how to apply the knowledge in practice (Barnes, 2014;Blair & Serafini, 2016;Masadeh, 2012;Rickman, 2004), although the distinction between training and education is not universally agreed, see for example Hager and Laurent (1990), and each term can be parsed in greater detail, for example in Garavan (1997). The importance of workplace learning is demonstrated in a survey of Finnish university graduates conducted by Tynjälä et al (2006), which revealed that 64 percent of the 990 respondents considered they had learned the most important skills for their jobs at work, rather than at university, while just 14 percent thought they had learned the skills at university.…”
Section: Introductionmentioning
confidence: 99%